Effect of Consortia Bioformulation of Rhizobacteria on Induction of Systemic Resistance in Tuberose Against Peduncle Blight Disease - Durgadevi, D.; Srivignesh, S.; Sankaralingam, A. (International Journal of Bio-resource and Stress Management, 2018)
Bioformulations of mixtures of plant growth promoting bacterial (Pseudomnas flourescences Pf1 Bacillus subtilis Bs10) and fungal isolates (Trichoderma viridae Tv1) were effective in reducing the incidence of peduncle blight under green-house conditions (85.50%). Peduncle blight, hitherto an unknown disease was found to be a major limiting factor to the cultivation of tuberose. Though Lasiodiplodia theobromae is an ubiquitous pathogen, its occurrence on tuberose is a new record in India. In addition to disease control, a significant increase in the yield (53.33%) was noticed in the bioprimed plants when compared to the control plants. Pathogenesis-related (PR) proteins, chitinase and b-1, 3-glucanase and defense-related proteins, peroxidase, polyphenol oxidase, phenylalanine ammonialyase and phenolic compounds were significantly activated in the consortia bioformulation treated plants, thus inducing resistance against Lasiodiplodia theobromae. Native gel electrophoresis also revealed the expression of more isoforms of pathogenesis-related proteins and other defense enzymes viz., polyphenol oxidase and peroxidase in plants treated with Pf1+Bs10 strain mixture challenged with L. theobromae. Populations of bacteria also remained high and stable throughout the growing period. The present study reveals that, microbe inoculated bulblets showed sustained, timely induction and accumulation of these defense enzymes and PR-proteins which enhances the resistance in tuberose against peduncle blight disease and also improved the vegetative growth, physiological attributes, PR-proteins and phenol contents.